Enhanced antimicrobial potency and stability of juglone/β-cyclodextrin inclusion complexes: a comparative study of formulation methods - Pelin Pelit Arayıcı; Tayfun Acar; Tülin Özbek; Serap Acar (Materials Research Express, 2024)
Juglone (5-hydroxy-1,4-naphthoquinone), a natural antifungal and antibacterial agent derived from walnut trees, possesses significant therapeutic potential limited by its low water solubility and instability in varying pH and temperature conditions This study aims to address these limitations by enhancing juglone’s solubility, stability, and antimicrobial efficacy through the formation of inclusion complexes with β -cyclodextrin ( β -CD). Employing methods such as co-precipitation, freeze-drying, and solvent evaporation, we synthesized these complexes and confirmed their formation using UV–vis, and FT-IR spectroscopy. The obtained optimum complex was characterized using SEM to reveal its structural properties, while NMR analysis showed significant chemical shift changes, indicative of complex formation between juglone and β -CD; additionally, XRD analysis confirmed the amorphous nature of the J- β -CD3-4 inclusion complex, providing direct evidence for its formation. Our findings reveal a notable enhancement in the pH and thermal stability of juglone within the β -CD inclusion complex, in comparison to its free form. Moreover, the antimicrobial activity of the juglone- β -CD complex surpassed that of juglone alone. The increased water solubility of juglone in the inclusion complex contributed to its enhanced antimicrobial activity. The inhibition zone diameters of J- β -CD3-4 inclusion complex against E. coli, S. aureus, and C. albicans were 7, 22, and 8.5 mm, respectively, relatively higher than juglone. Remarkably, in the broth microdluation method, the MIC and MBC values of the inclusion complex were determined to be much lower than those of free juglone, a significant fourfold decrease for S. aureus, and C. albicans and twofold for E. coli . These results underscore the potential of juglone- β -CD complexation in extending the applicability of juglone, especially in sectors such as food preservation, agriculture, and pharmaceuticals, where enhanced stability and efficacy of natural antimicrobial agents are crucial.